Metacognitive Short-Term Intervention in Patients With Mental Disorders Following Cardiovascular Events - Gebhardt, Philippa; Caldarone, Flora; Westhoff-Bleck, Mechthild; Olsson, Karen M.; Hoeper, Marius M.; Park, Da-Hee; Stapel, Britta; Breitner, Michael H.; Werth, Oliver; Heitland, Ivo; Kahl, Kai G. (Frontiers in Psychiatry, 2022)
Background Mental disorders are common among patients with severe cardiovascular diseases (CVD). Yet, there is a lack of easily accessible evidence-based treatments. Recent research indicates elevated prevalence of dysfunctional metacognitions in patients with mental disorders following cardiovascular events. As metacognitive therapy (MCT) is an established treatment to modify metacognitions, we tested if a brief metacognitive intervention via videotelephony is effective in this patient group. Methods A brief MCT treatment was tailored to CVD patients and designed as a face-to-face internet-based intervention. Five patients with CVDs and comorbid mental disorders underwent a psychocardiological examination and diagnostic approach. Each patient participated in eight 50 min sessions via encrypted video messenger service. Metacognitions, depression and anxiety symptoms and quality of life were assessed by self-report measures pre- and post-treatment. Patients rated dysfunctional thought processes, current psychological impairment, and treatment satisfaction after each session. Intended follow-up measures were not reported due to missing data. Results For most patients, the brief metacognitive intervention was associated with a decrease in dysfunctional metacognitions and a reduction of symptoms of anxiety and depression post-treatment. Psychological and physiological quality of life improved. Patients reported high satisfaction with the tailored treatment. Conclusion Our results suggest that a brief internet-based metacognitive treatment may be a promising tool for patients with CVDs and comorbid mental disorders. Feasibility and acceptance of the intervention was rated high by the patients. Further research is necessary to support the preliminary findings and to adapt and evaluate the intervention in a controlled clinical trial setting.